Tomorrow is Mom's birthday - Dorflinger, Carolyn (HongKong : Whispering Coyote Press, Inc, 1994)
Tomorrow is Mom's birthday and Tyler can't figure out what to give her, until he thinks of something really terrific.
Keywords: Birthdays -- Fiction; Gifts -- Fiction; Mothers and sons -- Fiction